Direction of special education teachers towards (inclusive education) integration of students with disabilities in public schools. "A field study in schools implementing the inclusive education process" - جلال, د. كارۆخ جوهر (Sulaimani Journal for Humanities, 2025)
The aim of this research is to investigate the attitudes of special education teachers towards the integration of students with special needs into government schools in Erbil Governorate. The researcher employed a descriptive method. The study population consisted of special education teachers working in inclusive schools in Erbil Governorate. A purposive random sample of 34 teachers—13 males and 21 females—was selected. The researcher developed the instrument based on the Attitudes of Special Education Teachers scale by Qasim (2022) and Saeed(2020). To determine the psychometric properties (validity and reliability) of the instrument, statistical analyses were conducted using SPSS, including the t-test. The results revealed that special education teachers generally hold positive attitudes toward integrating students with special needs into inclusive schools. However, the study also identified various difficulties and challenges associated with the integration process. Furthermore, there were statistically significant differences (α = 0.05) in teachers’ attitudes based on gender, with male teachers showing more favorable attitudes than their female counterparts. Based on the findings, the researcher offers several recommendations for future studies.
Keywords: Attitudes; Special Education Teachers; Integration; Students with Special Needs